Water Treatment Using Coagulant From Moringa Oliefera Seeds - Zulkefle, Mohamad Shawaluddin (Universiti Sains Malaysia, 2015)
Water related problem became global issue around the world. The usages are important in our daily life. Nowadays, many of the water sources were polluted with hazardous material. Therefore, the treatment of wastewater was needed. One of the processes in water treatment was coagulation and flocculation. Conventionally, aluminium sulphate was use as coagulant but it was said that would give some side effect. To replace it the use of natural coagulant was needed. Natural coagulant from plant like Moringa Oliefera was studied to know it composition and its ability to act as coagulant. The powder of Moringa Oliefera that has been extracted will be use as natural coagulant. This powder will be characterized using SEM and FTIR while the remaining powder will be use as natural coagulant. To know the ability of Moringa Oliefera coagulant, jar test experiment was conducted to know the parameter affecting this coagulant. From the experiment, it shows that extractes Moringa Oliefera powder contain hydrocarbon with aromatic ring and aliphatic amines that consist of nitro compound. During jar test experiment, the turbidity removal of colloidal material in the water was higher when the mixing rate and time of mixing was 30 rpm for 40 minute with 96.8% removal. While at higher turbidity, the removal was highest with optimum dosage of 50mg/L of coagulant with 95.6% removal. Lastly, at different range of water turbidity the turbidity removal were higher for optimum pH 7 and 8 with 93.8% and 96.7% removal. Therefore the use of this natural coagulant can be use as the replacement of conventional coagulant use in water treatment.